Community health workers as agents of change: Negotiating pathways of empowerment - Mahmud, Simeen; Sultan, Maheen (BRAC Institute of Governance and Development (BIGD), 2022)
In Bangladesh, health and family planning programs were the ﬁrst major employers of rural women in outside paid work. Thus, women community health workers became the pioneers in bringing rural women into outside formal employment in a social/economic context that not only discouraged women’s participation in paid outside work but also actively restricted their mobility in the public domain. Although for women today, working as community health workers is no longer a departure from the norm, this was not always the case. This paper looks at contemporary women health workers in Bangladesh to explore how they have re-negotiated purdah and social norms to emerge as valued members of their families and respected members of their communities. While the work of a health worker was itself an extension of women’s traditional care roles and was conceived precisely because norms around women’s visibility and seclusion were so strong at the time that women were difficult to reach with male health workers, this job has been able to negotiate norms to make women’s breadwinner roles and mobility in the public sphere more socially acceptable. It is noteworthy that in this process of change and continuity, women’s trade-oﬀs have been more diﬃcult within the sphere of family and their individual lives, and relatively easier in the sphere of community life. There was some evidence that the speciﬁc organizational context in which women worked had bearing upon these changes.